Renal and Cardiovascular Morbidities Associated with APOL1 Status among African-American and Non-African-American Children with Focal Segmental Glomerulosclerosis - Woroniecki, Robert P.; Ng, Derek K.; Limou, Sophie; Winkler, Cheryl A.; Reidy, Kimberly J.; Mitsnefes, Mark; Sampson, Matthew G.; Wong, Craig S.; Warady, Bradley A.; Furth, Susan L.; Kopp, Jeffrey B.; Kaskel, Frederick J. (Frontiers in Pediatrics, 2016)
Background and objectives African-American (AA) children with focal segmental glomerulosclerosis (FSGS) have later onset disease that progresses more rapidly than in non-AA children. It is unclear how APOL1 genotypes contribute to kidney disease risk, progression, and cardiovascular morbidity in children. Design, setting, participants, and measurements We examined the prevalence of APOL1 genotypes and associated cardiovascular phenotypes among children with FSGS in the Chronic Kidney Disease in Children (CKiD) study; an ongoing multicenter prospective cohort study of children aged 1–16 years with mild to moderate kidney disease. Results A total of 140 AA children in the CKiD study were genotyped. High risk (HR) APOL1 genotypes were present in 24% of AA children (33/140) and were associated with FSGS, p < 0.001. FSGS was the most common cause of glomerular disease in children with HR APOL1 (89%; 25/28). Of 32 AA children with FSGS, 25 (78%) had HR APOL1. Compared to children with low risk APOL1 and FSGS (comprising 36 non-AA and 7 AA), children with HR APOL1 developed FSGS at a later age, 12.0 (IQR: 9.5, 12.5) vs. 5.5 (2.5, 11.5) years, p = 0.004, had a higher prevalence of uncontrolled hypertension (52 vs. 33%, p = 0.13), left ventricular hypertrophy (LVH) (53 vs. 12%, p < 0.01), C-reactive protein > 3 mg/l (33 vs. 15%, p = 0.12), and obesity (48 vs. 19%, p = 0.01). There were no differences in glomerular filtration rate, hemoglobin, iPTH, or calcium–phosphate product. Conclusion AA children with HR APOL1 genotype and FSGS have increase prevalence of obesity and LVH despite a later age of FSGS onset, while adjusting for socioeconomic status. Treatment of obesity may be an important component of chronic kidney disease and LVH management in this population.